تأثير كتلة النيوترينو على المقطع العرضي لتشتته المرن على الالكترون ودورها في الانحراف عن النموذج المعياري للجسيمات الأولية في مجالي الطاقات المنخفضة والعالية (Latakia University Journal -Basic Sciences Series, 2018)
تم حساب المقطع العرضي التفاضلي للتشتت المرن للنيوترينو( مضاد النيوترينو ) على الإلكترون ، وتمت دراسة تأثير كتلة النيوترينو المختلفة عن الصفر على هذا المقطع العرضي للتشتت من خلال التفاعلات الفرميونية رباعية التمثيل بين المجالين( V , A ): و( S , P ) وتبيّن أن هناك انحرافاً عن النموذج المعياري للجسيمات الأولية جدير بالاهتمام.كتلة النيوترينو غير المعدومة أسهمت في هذا الانحراف. The differential cross section of elastic scattering of neutrino (antineutrino) on the electron was calculated. The influence of non zero neutrino mass on the elastic - scattering cross section was investigated in the framework of general four – fermions interaction (V, A) and (S, P) fields. The deviation of the results obtained from those predicted by the standard model of elementary particles was explained. The non zero mass of neutrino tacked part in the deviation.